The Relationship of 2D:4D Ratio and Hand Grip Strength to the Incidence of Multiple Sclerosis - Hamid Arazi; Roghayeh Bavafa Birak Olia; Shahriar Nafissi; Nahid Beladi Moghadam; Akram Falahati (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2018)
Regarding the muscular weakness in patients with Multiple and the importance of the 2nd digit to 4th digit (2D:4D) ratio as a representative of the androgen level in women, the aim of this study was to investigate the relationship between level of physical activity, handgrip strength and 2D:4D ratio with the incidence of multiple sclerosis. This cross-sectional study was conducted on 100 female patients with average age of 35.01 years, BMI 24.04 kg/m2 and disability development scale of Kurtzke (EDSS) equal to 8.5-0 among the patients of Shariati, Imam Hossein and Rasul Akram hospitals in Tehran in time intervals of December 2015 to June 2016. Hand grip strength variables were measured using the dynamometer, the 2D:4D ratio was measured with a digital calliper and the participants' physical activity were measured using the Beck physical activity questionnaire and EDSS of patients was determined by a Neurologist. The study data was analysed using statistical methods of Pearson and Spearman correlation analysis. There was a significant relationship between the physical activity level and EDSS (P<0.01) and the handgrip strength with the EDSS level (P<0.05) in MS patients. However, there was no significant relationship between the 2D:4D ratio and EDSS level. Based on these results, it seems that, the increase of physical activity level and the hand grip strength is associated with a reduced level of disability in patients with multiple sclerosis. Therefore, it is recommended to prescribe an exercise program which is in accordance with MS patients' condition.